Epitranscriptomic modifications in plant RNAs - Susheel S. Bhat; Michel Paul; Brian D. Gregory (RNA Biology)
A plethora of new and exciting findings have dramatically widened the horizons of plant RNA-related research. Despite being identified decades ago, RNA modifications were largely ignored owing to the immense difficulty in studying them with traditional methods. We now know that these chemical additions to RNA nucleotides affect a myriad of plant biological processes ranging from plant growth and development to stress responses. The field of epitranscriptomics, the study of RNA modifications, has been dominated by m6A in messenger RNAs (mRNAs), while modifications other than m6A remained largely unstudied. A recent increase in studies investigating other RNA modifications and the development of novel tools has added to the evolving landscape of plant epitranscriptomic research. As this non-m6A RNA modification research gathers pace, we use this review to provide a snapshot of the current state-of-the-art regarding these modifications with a focus on those occurring in functional non-coding RNAs as compared to mRNAs.